Aging with Diversity: Understanding the Challenges and Needs of LGBTI Elders in Nepal - Gurung, Bimala (International Research Journal of MMC (IRJMMC), 2025)
This study examines the unique challenges faced by Lesbian, Gay, Bisexual, Transgender and Intersex elders who are marginalized groups due to the intersection of age, sexual orientation, and gender identity. Despite advancements in life expectancy and legal recognition of LGBTI rights, these individuals often encounter discrimination, social isolation, and healthcare barriers. The Senior Citizens Act 2006 defines "senior citizens" as those aged 60 and above, but LGBTI elders frequently experience premature aging due to factors such as inadequate diet, social isolation, and informal sector labor conditions. Mapping of 100 LGBTI elders in 2024 was conducted across all seven provinces of Nepal. mong them, 20 core respondents were selected using purposive sampling with qualitative methods, including in-depth interviews with LGBTI elders and key informant interviews with experts. The study explores discrimination, access to healthcare, social support and perceptions of aging while secondary data sources include policy documents, reports, publications, media and research articles and video documentation. Findings reveal compounded challenges including economic insecurity and exclusion from social benefits, exacerbated by legal and policy gaps. The study advocates for explicit legal recognition, inclusive policies, and collaborative interventions to address these disparities and promote the rights of LGBTI elders in Nepal. It emphasizes the need to address the unique challenges faced by LGBTI elders in Nepal.